2008
DOI: 10.1002/em.20416
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metabolite profiles generated in Aroclor‐induced rat liver and human liver subcellular fractions: Considerations for in vitro genotoxicity hazard assessment

Abstract: Because it is well known that metabolites of chemicals and drugs are frequently the ultimate species responsible for genotoxicity and carcinogenicity, in vitro testing to identify the human genotoxicity hazard potential of new chemicals and drugs routinely utilizes liver S-9 fraction from rats treated with Aroclor 1254 as a system that can generate metabolites. However, it is frequently questioned as to whether such an in vitro metabolite generation system is the most relevant for human risk, or whether the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…We had also verified that the herein used rat liver S9-activation system, similarly to human liver S9 preparations or the classical double-induced S9 mix (Aroclor + phenobarbital or dexamethasone), has the capacity to convert AFB 1 to DNA reactive derivatives in vitro 29, 30. The rat liver S9-activation system is proven to contain cytochrome P450 3A4 and 1A2 enzymes 38 that are primarily involved in oxidative bioactivation of AFB 1 1214. Thus, we included the S9-activation system in our cytotoxicity experiments and established a relevant dosing range for AFB 1 , which served as a guideline for DNA adduct and mutagenesis experiments ( see , Fig.…”
Section: Discussionmentioning
confidence: 66%
“…We had also verified that the herein used rat liver S9-activation system, similarly to human liver S9 preparations or the classical double-induced S9 mix (Aroclor + phenobarbital or dexamethasone), has the capacity to convert AFB 1 to DNA reactive derivatives in vitro 29, 30. The rat liver S9-activation system is proven to contain cytochrome P450 3A4 and 1A2 enzymes 38 that are primarily involved in oxidative bioactivation of AFB 1 1214. Thus, we included the S9-activation system in our cytotoxicity experiments and established a relevant dosing range for AFB 1 , which served as a guideline for DNA adduct and mutagenesis experiments ( see , Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Some phase II enzymes, such as UDPglucuronosyltransferases (UGT), glutathione S-transferases (GST), sulfotransferase (SULT), or N-acetyl transferases, are not active in the reduced form of the nicotinamide adenine dinucleotide phosphate (NADPH)-supplemented S9 system (S9 mix) because other cofactors and additives (e.g., uridine diphosphate glucuronic acid, glutathione, acetylcoenzyme A, etc.) would be needed (Ku et al, 2007;Obach and Dobo, 2008). This can be essential not only for reducing potential false positives (e.g., reactive electrophiles that would be rapidly quenched by conjugation in vivo before being able to cause mutation) but also for false negatives because some conjugation reactions can yield metabolites that are more reactive than their substrate (e.g., sulfation of N-hydroxy-2-acetylaminofluorene or acetylation of N-hydroxylated heterocyclic amines) (Dashwood, 2002;Ku et al, 2007).…”
Section: Safety Pharmacologymentioning
confidence: 99%
“…This is because the system is set up to favor CYP-mediated metabolism and the other enzymes present in the system that could be responsible for detoxication of reactive intermediates are not supplemented with the appropriate cofactors (e.g., UGT, GST, methyl transferases, etc), thus potentially providing an unrealistic metabolic profile. In a recent work by Obach and Dobo, it was revealed that many human in vivo metabolites arise via conjugation reactions with the limited 16 drugs (Obach and Dobo, 2008). This can be important not only for reducing potential false positives (e.g., reactive electrophiles that would be rapidly quenched by conjugation in vivo before being able to cause mutation) but can also be important for false negatives because some conjugation reactions can yield metabolites that are more reactive than their substrate (e.g., sulfation of aliphatic alcohols or glucuronidation of carboxylic acids; [Glatt et al, 1998;Sallustio et al, 2006]).…”
Section: Genotoxic Assessment Of Chemicals Metabolized By Phase I Andmentioning
confidence: 99%
See 2 more Smart Citations